Distinguishing proof of the S-genotypes of a few sweet cherry (Prunus avium L.) cultivars by AS-PCR and fertilization - Wang Lee; Chain V. Zackie (Advances in Aquaculture and Fisheries Management, 2019)
Sweet cherry cultivars display a self-incompatibility system that restricts self-fertilization and fertilization between cultivars bearing identical S-alleles. PCR-based S-allele typing system for sweet cherry cultivars has been recently developed. It has been reported that all known self-incompatibility (S) alleles of sweet cherry were more than 16 based on the AS-PCR analysis. In this work, two sets of AS-PCR primers that were designed based on conserved domains of cDNA sequences of S-RNases has been used to characterize the S-genotype of 38 sweet cherry cultivars, including 15 cultivars whose S-genotype had not been previously described. Pollination test was also performed to validate the PCR results, and the consistent results were got. A wide variation in the frequency of Salleles in the Sweet cherry germplasm was observed. S3 was the most common in the cultivars evaluated, and S7, S10-S16, S23-S25 as rare allele was not found in China geographical areas in our study